Humor and eroticism in works written by contemporary female Spanish and French writers - Tremblais, Mathilde (Romanica Olomucensia, 2019)
This paper presents the issue of humour in French and Spanish contemporary erotic literature and, especially, in works written by women. The women who are studied in this paper are Regine Deforges, Francoise Rey, Alina Reyes, and Catherine Millet for French literature and Mercedes Abad, Ana Rossetti, Almudena Grandes, and Isabel Franc for Spanish literature. In the first place, the conceptual approach of connecting humour and erotisism, two concepts between which it is possible to establish various analogies, has been used. In the second place, a thematic and formal study has been carried out to identify the main distinctive characteristics that humour takes on in the erotic works of the selected women. The ambiguity, the unexpected, and the unusual are characteristics that typify humour in erotic literature. The confusion of genders, transgressions of the traditional literary conventions, or a crisis that tears up the 'Me' are issues that appear in the erotic texts and in the milieu in which humour likes to be introduced. This paper shows that even though some small differences appear, it is possible to establish various connections between humour as shown in the contemporary erotic works written by French women and those written by Spanish women.
Keywords: humour; eroticism; contemporary literature; female writers; France; Spain